Industry choice by young entrepreneurs in different country settings: the role of human and financial capital - Knatko, Dmitri; Shirokova, Galina; Bogatyreva, Karina (Journal of Business Economics and Management, 2016)
Entrepreneurial entry happens as a consequence of a general choice of an individual to become an entrepreneur. While most entrepreneurial entry studies rarely consider an industry choice to be an aspect of entrepreneurial decision making process, we address this issue taking into account individual, industrial, and country specific attributes. Using data from the Global University Entrepreneurial Spirit Students’ Survey (2013–2014) on young nascent entrepreneurs and extending it with objective indicators derived from World Bank, Global Entrepreneurship Monitor, and International Property Rights Index datasets, we investigate how various factors impact the choice between knowledge-intensive and capital-intensive industries. Drawing on the RBV and contingency approach, we link an industry choice to the level of human capital development and access to financial capital testing for possible country-specific moderation effects. Our study contributes to entrepreneurial entry research stream extending the understanding of entrepreneurial entry decision making nuances related to individual access to resources and both industryand country-level contingencies.